Vegetative growth, chemical composition, and flavonoids content of Azadirachta indica plants as affected by application of yeast natural extract - Lobna S. Taha,Soad M.M. Ibrahim,Nahed G. Abdel Aziz (Journal of Applied Pharmaceutical Science, 2016)
This experiment was carried out during 2013 and 2104 seasons on Azadirachta indica plants at National Research Centre greenhouse, Egypt. Experiment studied the effect of foliar spraying plants with dry yeast (Saccharomyces cerevisiae) extract at various concentrations (0, 5, 10, 15 and 20%) on growth, pigments, NPK (%), total soluble sugars, indoles, phenols and flavonoids leaves contents. Results showed that spraying neem plants with yeast extract at 15% significantly increased growth parameters (plants height, stem and root fresh and dry weights) and enhanced total chlorophylla, phosphorus, potassium and total soluble sugars content. Using the concentration 5% of dry yeast extract gave the highest values of chlorophyll b, total carotenoids and total chlorophyll content. Nitrogen content was produced at the highest value (3.55%) in plants treated with dry yeast extract at 10%.The foliar application of yeast extract at 10, 15 and 20% resulted the highest values of total soluble phenols (72.48, 72.27 and 73.46 mg/g D.W., respectively). The highest flavonoids leave content (3.23 and 3.14 mg CE/g D.W.) were obtained when the dry yeast extract was used at 15 and 20%, respectively. On the other hand, all treatments had no significant effect on stem diameter, number of leaves /plant and root length.
Keywords: Saccharomyces cerevisiae,yeast,Neem plants,pigments,mineral,Phenolic content.